Предмет: Математика, автор: g9201573

2(x-2)(x+2)-(x-1)²=x2-5сроснл

Ответы

Автор ответа: kirillantonchuk
1

Відповідь:Let's start by expanding the left-hand side of the equation:

2(x-2)(x+2)-(x-1)² = 2(x²-4)-(x²-2x+1) = 2x²-8-x²+2x-1 = x²+2x-9

So, the original equation becomes:

x²+2x-9 = x²-5

Subtracting x² from both sides, we get:

2x-9 = -5

Adding 9 to both sides, we get:

2x = 4

Dividing by 2, we get:

x = 2

Therefore, the solution to the equation is x = 2.

Покрокове пояснення:

Похожие вопросы
Предмет: Геометрия, автор: EgorSasenow